Prevention of depression and anxiety symptoms in adolescents: 42 and 54 months follow-up of the Aussie Optimism Program-Positive Thinking Skills - Johnstone, Julie; Rooney, Rosanna M.; Hassan, Shari; Kane, Robert T. (Frontiers in Psychology, 2014)
Anxiety and depression are the most commonly reported mental health problems amongst Australian children and adolescents. The Aussie Optimism Program: Positive Thinking Skills (AOP- PTS) is a universal intervention program based on cognitive and behavioral strategies and aimed to prevent anxiety and depression in the middle primary school children aged 9-10 years old. 370 students randomly assigned to the intervention and control condition participated in the 42 and 54 months follow – up study. The intervention group received the AOP-PTS 10-week program and the control group received the regular Health Education curriculum. Students were assessed on anxiety, depression and attribution style at school whilst parents reported on their child’s externalizing and internalising problems at home. Results showed there were no significant reduction across groups in the depressive and anxiety symptoms, and attribution style at either 42 or 54 months follow-up. These findings suggest that AOP-PTS has short and medium term effects but were not sustained in longer term period. Future strategies to achieve the desirable outcomes in a longitudinal study are discussed.